2022
DOI: 10.1007/s00441-022-03635-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the relaxin family peptide 4 receptor by enterochromaffin cells of the mouse large intestine

Abstract: The gastrointestinal hormone, insulin-like peptide 5 (INSL5), is found in large intestinal enteroendocrine cells (EEC). One of its functions is to stimulate nerve circuits that increase propulsive activity of the colon through its receptor, the relaxin family peptide 4 receptor (RXFP4). To investigate the mechanisms that link INSL5 to stimulation of propulsion, we have determined the localisation of cells expressing Rxfp4 in the mouse colon, using a reporter mouse to locate cells expressing the gene. The fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(48 reference statements)
2
4
0
Order By: Relevance
“…However, IGFBP3 has been implicated in regulation of gut stem cell proliferation and differentiation [ 29 ]. Interestingly, we also saw a small amount of GCG co-expression with RXFP4 which agrees with a recent immunohistological analysis of mouse gut that found a small amount of RXFP4 co-expression with Oxyntamodulin [ 15 ]. We looked at TPH2 and TAC1 to indicate the presence of enteric neuronal cell types but found little evidence for co-expression of RXFP4, although these markers were only expressed in a few cells suggesting these cell types were not sufficiently surveyed in these datasets.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, IGFBP3 has been implicated in regulation of gut stem cell proliferation and differentiation [ 29 ]. Interestingly, we also saw a small amount of GCG co-expression with RXFP4 which agrees with a recent immunohistological analysis of mouse gut that found a small amount of RXFP4 co-expression with Oxyntamodulin [ 15 ]. We looked at TPH2 and TAC1 to indicate the presence of enteric neuronal cell types but found little evidence for co-expression of RXFP4, although these markers were only expressed in a few cells suggesting these cell types were not sufficiently surveyed in these datasets.…”
Section: Discussionsupporting
confidence: 92%
“…Most 5-HT positive cells have some Rxfp4 speckles, however there is Rxfp4 signal in areas not positive for 5-HT. This aligns with immunohistological analysis of a Rxfp4-reporter mouse where full quantification showed co-expression to vary across the lower GI tract, over 90% of 5-HT-positive cells were also immunoreactive for GFP [ 15 ]. These findings make it clear that INSL5-RXFP4 signalling has great potential to affect serotonin synthesis and/or secretion from EC cells.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The expression of Insl5 and Rxfp4 mRNA has been detected in the pancreas, thymus and in the gastrointestinal tract, 202,291 particularly in the L‐cells of distal gut 292–294 ; INSL5 has been shown to function as an orexigenic hormone, 291 and to influence colonic propulsion, 232,295 immune cell function, 296 and even human sperm motility 297 . Finally, a recent study identified a potential role for INSL5 (or relaxin‐3) signaling via ventral hypothalamic RXFP4 in the control of high‐fat and high‐protein diet consumption in mice 298 .…”
Section: Insulin‐like (Relaxin)‐family Peptide and Receptor Systemsmentioning
confidence: 99%